Development of Swimming Abilities in Squid Paralarvae: Behavioral and Ecological Implications for Dispersal - Vidal, Erica A. G.; Zeidberg, Louis D.; Buskey, Edward J. (Frontiers in Physiology, 2018)
This study investigates the development of swimming abilities and its relationship with morphology, growth and nourishment of reared Doryteuthis opalescens paralarvae from hatching to 60 days of age at 16 °C. Paralarvae (2.5-11 mm mantle length-ML) were videotaped and their behavior quantified throughout development using computerized motion analysis. Hatchlings swim dispersed maintaining large nearest neighbor distances (NND, 8.7 ML), with swimming speeds (SS) of 3-8 mm s-1 and paths with long horizontal displacements, resulting in high net to gross displacement ratios (NGDR). For 15 day-old paralarvae, swimming paths are more consistent between jets, due to growth of fins, and increases in length and mass. The swimming pattern of 18 day-old paralarvae starved for 72 h exhibited a significant reduction in mean SS and inability to perform escape jets. A key morphological, behavioral and ecological transition occurs at about 6 mm ML (>40 day-old), when there is a clear change in swimming performance and behavior, paths are more regularly repeated and directional swimming is evident. These squid are able to perform sustained swimming and hover against a current at significantly closer NND (2.0 ML), as path displacement is reduced and manuverability increases. Social feeding interactions (kleptoparasitism) are often observed prior to the formation of schools. As paralarvae reach 35-45 day-old, they are able to attain speeds up to 562 mm s-1 and to form schools; their swimming pattern showed enhanced control of jetting and maneuvering. Schools are always formed within areas of high flow gradient in the tanks and are dependent on size and current speed. Fin development is a requisite for synchronized and maneuverable swimming of schooling juveniles. Although average speeds of paralarvae are within intermediate Reynolds numbers (Re <100), they make the transition to the inertia-dominated realm during escape jets of high propulsion (Re>3200), transitioning from plankton to nekton after their first month of life. The development of swimming capabilities and social interactions enable juvenile squid to school and accelerate orientation and cognition. These observations indicate that modeling of the lifecycle should include competency to exert influence over small currents and dispersal patterns after the first month of life.